Endoscopic lung volume reduction: an expert panel recommendation - Herth, Felix; Slebos, Dirk-Jan; Rabe, Klaus F.; Shah, Pallav (Respiration, 2016)
Chronic obstructive pulmonary disease (COPD) is a progressive condition comprising a constellation of disorders from chronic bronchitis, airflow obstruction through to emphysema. The global burden of COPD is estimated at more than 6% of the population. The standard of care is based on a combination of smoking cessation, immunization, pharmacological treatments and pulmonary rehabilitation. However, the more advanced stages of COPD are challenging to manage. In this situation, our current standards of care do not adequately control patient symptoms nor halt the progressive decline. For the emphysema phenotype, lung volume reduction surgery has shown a beneficial effect in selected patients but is counterbalanced by the morbidity experienced by some patients. Bronchoscopic volume reduction technologies have been developed to improve the clinical situation of emphysema patients. This expert statement provides broad guidance regarding patient selection and the current position of the available techniques for patients with advanced emphysema.